Economic and Social Benefits and Challenges in the Infrastructure Projects Implementation in a Component City in Negros Occidental - Rogelio Raymund I. Tongson, Jr.,; Caelian, Merlita (Technium Social Sciences Journal, 2024)
Implementation of infrastructure projects is a critical aspect of achieving sustainable development, especially in archipelagic countries like the Philippines. Hence, this study determined the extent of economic benefits (employment, income, and food security) and social benefits (health, education, safety, security, and environmental protection) from infrastructure projects. It also compared the differences in benefits when communities are grouped based on sectoral divisions and geographical locations. Additionally, the study explored challenges faced by implementers. The research design was descriptive-comparative, with 440 respondents selected through stratified random sampling. A researcher-made questionnaire, validated and reliability tested using Lawshe’s content validation ratio and Cronbach’s alpha method, assessed the economic and social benefits. Data analysis involved descriptive statistics and non-parametric tests (Kruskal Wallis). Overall, the economic benefits received a very high rating, with income being the highest-rated attribute. Social benefits were also highly rated, with environmental protection receiving the highest score. Notably, the differences were observed based on geographical location and sectoral groups. Despite challenges, the study suggests that local government units can effectively manage large-scale infrastructure projects, contributing to inclusive and sustainable industrialization. The emphasis on environmental protection underscores the growing concern for climate change resilience.